Effect of blood flow–restricted resistance training on myocardial fibrosis in early spontaneously hypertensive rats - Tan, Zhaowen; Chen, Peiyou; Zheng, Yuchan; Pan, Ying; Wang, Baolong; Zhao, Yan (Frontiers in Cardiovascular Medicine, 2023)
Objective: The purpose of this study was to explore the effect of blood flow–restricted resistance training on myocardial fibrosis in early spontaneously hypertensive rats (SHRs). Methods: Four-week-old male Wistar-Kyoto rats and SHRs were randomly divided into the following groups: normal group (WKY), SHR control (SHR-SED) group, high-intensity resistance training (HIRT) group, low- and medium-intensity resistance training (LMIRT) group, and blood flow–restricted low- and medium-resistance training (BFRT) group. Body weight, hemodynamics, cardiac function, myocardial morphology and fibrosis, and the expression levels of transforming growth factor-beta1-Smad (TGFβ-1-Smad) pathway-related proteins in the myocardium were assessed. Results: 1) BFRT lowered blood pressure significantly, decreased left ventricular wall thickness, and improved cardiac function. At the same time, BFRT was superior to traditional resistance training in lowering diastolic blood pressure, and was superior to HIRT in improving left ventricular compliance, reducing heart rate, and reducing left ventricular posterior wall and left ventricular mass (P < 0.05). 2) BFRT decreased collagen I and collagen fiber area in the myocardium, increased the collagen III area, and decreased the collagen I/III ratio (P < 0.05). BFRT produced a better proportion of myocardial collagen fibers than did traditional resistance training (P < 0.05). 3) In the myocardium of the BFRT group compared to the traditional resistance training group, the expression of TGFβ-1, Smad2/3/4, p-Smad2/3, CTGF, and TIMP1 was significantly downregulated, MMP2 and TIMP2 were significantly upregulated, the MMP/TIMP ratio significantly increased, and TGFβ-1 expression significantly decreased (P < 0.05). Conclusion: BFRT inhibited the TGFβ-1-Smad pathway in the myocardium, downregulated the expression of CTGF, and regulated the balance between MMPs and TIMPs, thereby reducing myocardial fibrosis in SHR, and improving cardiac morphology and function. BFRT also lowered blood pressure, and achieved an effect of early prevention and treatment of hypertension. At the same time, BFRT was superior to traditional resistance training in reducing diastolic blood pressure and adjusting the proportion of myocardial collagen fibers.